Dionysus resurrected : performances of Euripides' 'The Bacchae' in a globalizing world - Fischer-Lichte, Erika (Blackwell Bristol lectures on Greece, Rome and the classical tradition, 2014)
Dionysus Resurrected analyzes the global resurgence since the late 1960s of Euripides’ The Bacchae. By analyzing and contextualizing these modern day performances, the author reveals striking parallels between transformational events taking place during the era of the play’s revival and events within the play itself.